2019
DOI: 10.3390/nu11122937
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D and Omega-3 PUFAs in Islet Transplantation

Abstract: Recurrence of autoimmunity and allograft rejection represent major challenges that impact the success of islet transplantation. Despite the remarkable improvements achieved in immunosuppression strategies after the publication of the Edmonton protocol, long-term data of intra-hepatic islet transplantation show a gradual decline in beta-cell function. Therefore, there is a growing interest in the investigation of novel, safe and effective anti-inflammatory and immunomodulatory strategies able to promote long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 116 publications
0
19
0
Order By: Relevance
“…A 25(OH)D serum level below 50 nM may lead to musculoskeletal disorders, such as rickets in children and osteomalacia and fractures in adults 6 . Moreover, vitamin D insufficiency is linked to a large set of immunologic disorders, such as multiple sclerosis 7 , inflammatory bowel disease 8 , rheumatoid arthritis 9 , type I diabetes 10 , or infections like tuberculosis 11 as well as to cancers of colon, breast, prostate and blood 12 . Furthermore, individuals differ in their response to supplementation with vitamin D 3 , such as biochemical and physiological changes 13 , which led to the concept of the personal vitamin D response index 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A 25(OH)D serum level below 50 nM may lead to musculoskeletal disorders, such as rickets in children and osteomalacia and fractures in adults 6 . Moreover, vitamin D insufficiency is linked to a large set of immunologic disorders, such as multiple sclerosis 7 , inflammatory bowel disease 8 , rheumatoid arthritis 9 , type I diabetes 10 , or infections like tuberculosis 11 as well as to cancers of colon, breast, prostate and blood 12 . Furthermore, individuals differ in their response to supplementation with vitamin D 3 , such as biochemical and physiological changes 13 , which led to the concept of the personal vitamin D response index 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency is highly prevalent following solid organ transplantation [226]. Pre-clinical studies showed that vitamin D and its analogs have beneficial effects in terms of islet graft survival and prevention of allograft rejection and recurrence of autoimmunity in animal models of syngeneic and allogeneic islet transplantation [227]. Therefore, vitamin D supplementation has been suggested as a valid therapeutic strategy to reduce opportunistic infections and prevent allograft rejection after solid organ and cell transplantation [226,227].…”
Section: Synergistic Anti-inflammatory and Immunomodulatory Effects Of Vitamin D And Dpp-4 Inhibitors: Mechanistic Evidencementioning
confidence: 99%
“…Pre-clinical studies showed that vitamin D and its analogs have beneficial effects in terms of islet graft survival and prevention of allograft rejection and recurrence of autoimmunity in animal models of syngeneic and allogeneic islet transplantation [227]. Therefore, vitamin D supplementation has been suggested as a valid therapeutic strategy to reduce opportunistic infections and prevent allograft rejection after solid organ and cell transplantation [226,227]. In this regard, Zhou et al [228] found that vitamin D deficiency represents an independent risk factor for acute cellular rejection after liver transplantation.…”
Section: Synergistic Anti-inflammatory and Immunomodulatory Effects Of Vitamin D And Dpp-4 Inhibitors: Mechanistic Evidencementioning
confidence: 99%
“…113,114 Anti-inflammatory effects of vitamin D are also implicated in successful organ transplantation. 73,[115][116][117][118] In endotoxin-induced acute respiratory distress syndrome (ARDS), inadequate vitamin D level is associated with increased levels of inflammatory cytokines such as IL-1 and TNF-. 119,120 In contrast to largely beneficial effects of vitamin D, certain infections (e.g., citrobacter and leishmania) were confusingly enhanced or unaffected by vitamin D. Subsequent categoric immunologic studies revealed inhibitory effects of vitamin D on inflammatory T H1 effector subset necessary for pathogen control.…”
Section: Disease Context-dependent Regulation Of Host Immunity By Vitamin Dmentioning
confidence: 99%